Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1007/s13361-012-0359-1
|View full text |Cite
|
Sign up to set email alerts
|

The Hydrogen–Deuterium Exchange at α-Carbon Atom inN,N,N-Trialkylglycine Residue: ESI-MS Studies

Abstract: Derivatization of peptides as quaternary ammonium salts (QAS) is a known method for sensitive detection by electrospray ionization tandem mass spectrometry. Hydrogens at α-carbon atom in N,N,N-trialkylglycine residue can be easily exchanged by deuterons. The exchange reaction is base-catalyzed and is dramatically slow at lower pH. Introduced deuterons are stable in acidic aqueous solution and are not back-exchanged during LC-MS analysis. Increased ionization efficiency, provided by the fixed positive charge on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
10

Relationship

8
2

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 13 publications
(16 reference statements)
1
25
0
Order By: Relevance
“…The ESI‐MS analysis revealed the complete HDX for the oligosarcosine peptide after 10 days at room temperature. Additionally, we observed that in the case of the α ‐C hydrogens of the N,N,N ‐trialkylglycine (betaine) residue in peptides, described by us previously , the H/D exchange occurs within 1 min, which suggests the effect of the quaternary ammonium group on the acidity of the α ‐C hydrogens . We have also found the possibility of such HDX at the α ‐C of the N ‐methyl alanine residue in peptides derivatized by a quaternary ammonium group .…”
Section: Introductionsupporting
confidence: 71%
“…The ESI‐MS analysis revealed the complete HDX for the oligosarcosine peptide after 10 days at room temperature. Additionally, we observed that in the case of the α ‐C hydrogens of the N,N,N ‐trialkylglycine (betaine) residue in peptides, described by us previously , the H/D exchange occurs within 1 min, which suggests the effect of the quaternary ammonium group on the acidity of the α ‐C hydrogens . We have also found the possibility of such HDX at the α ‐C of the N ‐methyl alanine residue in peptides derivatized by a quaternary ammonium group .…”
Section: Introductionsupporting
confidence: 71%
“…The second procedure was based on the H/D exchange of α-C hydrogens described previously for non-aromatic betaine derivatives ( N,N,N ,-trialkyloglycine)33. This method is limited to peptides containing the quaternary salt at the N-terminal α-amino acids, but cannot occur on the lysine side chain.…”
Section: Resultsmentioning
confidence: 99%
“…For this purpose, we designed and synthesized a series of oligoproline peptides derivatized with QAS. We performed ESI-MS/MS experiments on M + ions of all the synthesized QAS-peptide derivatives and, with the aid of base-catalyzed hydrogen/deuterium exchange, described by us previously [19], we examined the charge remote fragmentation mechanism, using collision-induced dissociation (CID).…”
Section: Introductionmentioning
confidence: 99%